Governing independence and expertise : the business of housing associations - McDermont, Morag (Hart Pub., 2010)
"Governing Independence and Expertise tells the story of the not-for-profit housing sector in England, focusing on its representative body, the National Housing Federation. The story tells of how the Federation and associations influenced their own space of governing through deploying discourses of independence and expertise; how being governed, and governing, become, at times, one and the same."--Jacket